Merek Sunan Drajat Garam Sehat Berkhasiat sebagai Merek yang Tidak Dapat Didaftarkan : Trademark “Sunan Drajat Garam Sehat Berkhasiat” as an Unregistrable Trademark - Neviar Amira Emor; Dian Purnamasari (Reformasi Hukum Trisakti, 2024)
There is legal ineffectiveness related to the conditions of trademarks that cannot be registered and can be rejected as stated in the fourth chapter of Law Number 20 Year 2016 on Trademarks and Geographical Indications (MIG Law). This legal scientific work discusses whether the trademark “Sunan Drajat – Garam Sehat Berkhasiat” can be categorized as an unacceptable trademark under the MIG Law because it contains elements of a famous person's name and claims to have efficacious products. This research is normative legal research and is descriptive, using secondary data obtained through literature studies. The data is processed qualitatively and conclusions are drawn using deductive logic. Based on the results, there are discrepancies in the implementation of the MIG Law, especially Articles 20 and 21, in processing trademark applications in Indonesia. The trademark “Sunan Drajat – Healthy Salt Efficacious” uses the name of a famous person and should be refused registration. Additionally, it uses the word "Efficacious," which needs further examination because it can cause confusion if the description is not accurate. The conclusion is that the mark should not be registered at the Directorate of Trademarks and Geographical Indications under Article 20 letter d of the MIG Law.